Diagnostic yield of induced sputum and Bronchoalveolar lavage in suspected pulmonary tuberculosis - Maria Musso; Gina Gualano; Paola Mencarini; Annelisa Mastrobattista; Maria Angela Licata; Carlo Pareo; Carlotta Cerva; Silvia Mosti; Virginia Di Bari; Raffaella Libertone; Carla Nisii; Angela Cannas; et al. (BMC Infectious Diseases)
Abstract Aim of this study was to compare the diagnostic yield of induced sputum (IS) and bronchoalveolar lavage (BAL) in patients with suspected pulmonary tuberculosis (PTB) and negative sputum smears. We enrolled 215 patients who underwent both IS and BAL after two negative spontaneous sputum samples. PTB was confirmed by culture or molecular test in 26 patients (12.1%). IS detected 10 cases (38.5%) of all PTB, while BAL detected 22 cases (84.6%) of all PTB. IS had a sensitivity of 38.46% and a specificity of 100%, while BAL had a sensitivity of 84.62% and a specificity of 100%. BAL had a higher diagnostic yield than IS and was useful for ruling out alternative diagnoses. According to our experience FBS execution is mandatory in case of strong TB suspicion and sputum smear negative patients, especially in a low TB prevalence country. Moreover, it consents testing microorganism sensitivity and assessing possible alternative diagnosis with similar clinical presentation. The choice of the best diagnostic method may depend on the clinical context and the availability of resources.